Impact of intensive management on the carbon flux variation characteristics of the Lei bamboo (Phyllostachys praecox) forest - Mingxia Zhang; Guangyong You; Yan Wang; Ruiqiang Yan; Changxin Zou; Shulin Chen (Global Ecology and Conservation, 2024)
The development of the China Certified Emission Reduction (CCER), a carbon sink project for bamboo afforestation and bamboo management at different scales, has been carried out in regions rich in bamboo resources. However, economically important bamboo forests are usually subjected to intensive management (IM) to increase the output of bamboo shoots and improve economic benefits. The carbon fixation capacity of bamboo forests often varies with the management methods, which has become a key factor affecting the accurate estimation of the value of bamboo afforestation and bamboo management carbon sink CCER projects. The effects of operation and management methods on carbon sinks are a matter of general concern. Owing to the lack of continuous observational data, there is no consensus on this matter. For this reason, in the present study, the Lei bamboo forest from Taihuyuan Town, Lin’an City, Zhejiang Province, China is used to study the variation of net ecosystem productivity (NEP), gross primary productivity (GPP), ecosystem respiration (Re) and the Rs under IM. The objective of this study is to determine the effect of IM on the carbon-fixing ability of the Lei bamboo forest ecosystem. Our results suggest that there were significant differences in NEP, GPP, Re, and soil carbon emissions between IM and non-intensive management (NIM), excluding the influence of meteorological factors. Specifically, on a seasonal scale, digging bamboo shoots and cutting old bamboo stems in the spring in the IM years led to a 72.28% decrease in NEP compared with that in the NIM years; hooking tips and trimming diseased branches in autumn had little effect on NEP (only −6.79%); irrigating in summer increased NEP by 22.4% and effectively avoided the impact of high temperature and drought on the bamboo forest. Notably, organic mulching and digging new bamboo shoots in winter led to an increase in the carbon emissions of the Lei bamboo forest in the winter of the IM years that was 6.75 times higher than that in the NIM years, reducing the NEP by 51.27%. Organic mulching was found to be an important reason why bamboo forests become extremely powerful carbon sources in winter (cumulative NEPaverage = - 35.31 gC m−2). On an interannual scale, the average NEP of the Lei bamboo forest in the IM years (108.98 gC m−2 yr−1) decreased by 29.93% compared to that of the NIM years (141.59 gC m−2 yr−1), and the total soil carbon emissions increased by 1.92 times. The results of this study show that IM might increase soil carbon emissions in the Lei bamboo forest ecosystem and reduce the NEP of the Lei bamboo forest.